France, Russia and Early Interchangeability in Firearms. (3rd July 2019) - Smithurst, Peter
Abstract : Many popular accounts, as well as some learned studies, credit America with the development of interchangeability in firearms. This view is incorrect. Anyone who has even glanced at this aspect of firearms history will have encountered the name of Honoré Blanc, designer of the iconic Modèle 1777 Fusil d'infanterie which was to have a profound influence on firearms design, and his claim to have achieved interchangeability of lock components. Less well known, perhaps, is that a similar claim was made in Russia in the first quarter of the nineteenth century. Despite these claims, they do not seem to have inspired later study; this article suggests that both claims were true.